Effects of different diets on growth performance, digestive enzyme activities and intestinal bacterial community of juvenile Chinese giant salamander (Andrias davidianus) - Jing Qian; Yao Wu Zhang; Li Yi; Ming Yan Shi; Dun Deng (Aquaculture Reports, 2023)
This study analyzed the growth performance, digestive enzyme activities and intestinal microbial community in HC group (fed with Chironomid larvae), HH group (fed with Chironomid larvae plus Earthworms) and QY group (fed with Earthworms) of juvenile Chinese giant salamander (Andrias davidianus) after farming for 60 days. The results showed that diet can affect the growth performance, digestive enzyme activities and intestinal mcirobiota composition of juvenile Chinese giant salamander. The growth performance in juvenile Chinese giant salamander of HC group was significantly higher than that of HH group and QY group. The ether extract content in muscles of juvenile Chinese giant salamander of HH group and QY group was significantly lower than that of HC group. The intestinal digestive enzyme activities in juvenile Chinese giant salamander of HC group were significantly lower than that of HH group and QY group. The intestinal microbial richness and diversity in juvenile Chinese giant salamander of HH group and QY group were significantly higher than that of HC group. The most dominant phylum of HC group and HH group was Firmicutes but QY group was Bacteroidota, and the most dominant genus of HC group was Clostridium_sensu_stricto_1 but HH group and QY group was Bacteroides. The 24 specific bacterial groups with different classification levels had significant differences in three diet groups of juvenile Chinese giant salamander and these specific bacteria were concentrated in Firmicutes, Proteobacteria and Bacteroidota. Thus, the above studies indicated that Chironomid larvae as diet can increase the growth performance of juvenile Chinese giant salamander, while the addition of Earthworms as diet can enhance digestive ability and change microbiota composition in intestine of juvenile Chinese giant salamander.